Evidence for widespread cryptic sexual generations in apparently purely asexual Andricus gallwasps - GRAHAM N. STONE; RACHEL J. ATKINSON; ANTONIS ROKAS; JOSÉ‐LUIS NIEVES ALDREY; GEORGE MELIKA; ZOLTAN Ács; GYÖRGY CSÓKA; ALEXANDER HAYWARD; RICHARD BAILEY; CAROLINE BUCKEE; GILEAN A. T. McVEAN (Molecular Ecology, 2008)
Oak gallwasps (Hymenoptera, Cynipidae, Cynipini) are one of seven major animal taxa that commonly reproduce by cyclical parthenogenesis (CP). A major question in research on CP taxa is the frequency with which lineages lose their sexual generations, and diversify as purely asexual radiations. Most oak gallwasp species are only known from an asexual generation, and secondary loss of sex has been conclusively demonstrated in several species, particularly members of the holarctic genus Andricus. This raises the possibility of widespread secondary loss of sex in the Cynipini, and of diversification within purely parthenogenetic lineages. We use two approaches based on analyses of allele frequency data to test for cryptic sexual generations in eight apparently asexual European species distributed through a major western palaearctic lineage of the gallwasp genus Andricus . All species showing adequate levels of polymorphism (7/8) showed signatures of sex compatible with cyclical parthenogenesis. We also use DNA sequence data to test the hypothesis that ignorance of these sexual generations (despite extensive study on this group) results from failure to discriminate among known but morphologically indistinguishable sexual generations. This hypothesis is supported: 35 sequences attributed by leading cynipid taxonomists to a single sexual adult morphospecies, Andricus burgundus, were found to represent the sexual generations of at least six Andricus species. We confirm cryptic sexual generations in a total of 11 Andricus species, suggesting that secondary loss of sex is rare in Andricus .